No evidence for effect of exercise on transcriptome of NK cells in breast cancer patients undergoing adjuvant therapy: results from a pilot study - Pal, Anasua; Zimmer, Philipp; Schmidt, Martina; Hummel, Manuela; Ulrich, Cornelia; Wiskemann, Joachim; Steindorf, Karen (Frontiers in physiology, 2019)
Background: Mobilization and activation of natural killer cells (NK cells) have been hypothesized to contribute to observed protective effects of exercise on cancer development and progression. Some evidence exists for acute effects of aerobic exercise on NK cell mobilization and function, i.e. alteration of the gene expression profile of NK cells. Yet, the chronic effects of exercise training, and effects of other modalities than endurance exercise are still understudied. Here, we investigated the chronic effects of a 12-week resistance exercise program on NK cell gene expression in breast cancer patients undergoing adjuvant chemo- or radiotherapy. Methods: Breast cancer patients were randomly assigned to either a 12-week resistance exercise program or a relaxation control group concomitant to adjuvant therapy. In a subsample of 19 participants, RNA was extracted from magnet bead isolated NK cells and subsequently analysed for differential gene expression using microarray Illumina HumanHT-12 v4 before and after the intervention. Results: After chronic exercise intervention several genes showed higher differential expression compared to the control group. However, after correction for multiple testing, baseline-adjusted analyses of covariance (ANCOVA) indicated no significant differences between the intervention and the control group with regard to the gene expression profile. Discussion: Our findings suggest that 12-week resistance-exercise did not alter the gene expression profile of NK cells in breast cancer patients undergoing adjuvant therapy on the long term. Further studies with larger sample sizes and specifically designed to investigate whether exercise-induced changes in NK cell function are attributed to acute effects are warranted.
Gesehen am 06.03.2020